RENEWABLE ASPHALT PAVEMENT: A BIBLIOMETRIC SYSTEMATIC LITERATURE REVIEW ON CHALLENGES, METHODOLOGIES, AND INNOVATIONS - Paikun Paikun; Lisa Oksri-Nelfia; Astri Rinanti; Sri Wiwoho Mudjanarko; Basil David Daniel; Williams Dunu (Universitas Trisakti, 2025)
Aims: This study aimed to investigate the challenges, methodologies, and innovations in the development of renewable asphalt pavements. It focused on evaluating the long-term performance, structural stability, and durability of renewable materials compared to conventional asphalt, while also identifying economic, regulatory, and technical barriers to their implementation. Methodology and results: A bibliometric systematic review was conducted using Scopus, following the PRISMA protocol. Co-occurrence and citation network analyses identified research trends and gaps. Findings reveal that reclaimed asphalt pavement (RAP) can reduce CO₂ emissions by 29.3%, while piezoelectric sensors in hot mix asphalt (HMA) can generate 76.56 MWh/month. Basalt fiber enhances hydrothermal resistance, and RAP in concrete improves shrinkage resistance with minor strength and density reductions. Conclusion, significance, and impact study: This research provides a comprehensive overview of renewable asphalt pavement, underscoring both its environmental benefits and current limitations. The insights provide valuable guidance for researchers, industry stakeholders, and policymakers in developing innovative and sustainable road infrastructure solutions. Future research should address the identified gaps to accelerate the adoption of renewable solutions in road construction.